Foltin and Claude “levi-skroz” [Poetry readings of the music of “Foltin”] - Деловски, Влатко (Poznańskie Studia Slawistyczne, 2012)
Foltin is a musical community, and I say community and not group, because the word group is associated with the crowd. This is my attempt totry to explain the process of reading the important  characteristics  of  purposeful  meaning  in  the  poetry  of  Branko  Nikolov  (Foltin). This kind of reading is qualitatively different from ordinary reading. Namely, we will dare to read  from  an  ethnographic  point  of  view,  which  means  investigating,  i.e.  analyzing  with active  participation.  From  the  end  of  the  1990s  until  today,  I  have  attended  all significant “Foltin” events, which for me is something private, and therefore something that engages me is  our  common  Vezilka,  their  poetry.  Hence,  reading  is  a  job  for  our  Vezilka  –  Lenka  or as they prefer to say, the song  120, while simple reading is a matter of my ignorance. From the  surface  level  of  their  explicit manifestation  (Music  and  Poetry),  everything  leads  to a  tangled,  implicit poetic  level.  That  is  the  process  that  we  technically  name  reading,  and reading looks like the one term that can be clearly marked as decoding from surface to deep structures.